2017
DOI: 10.1111/imm.12744
|View full text |Cite
|
Sign up to set email alerts
|

Expression and trafficking of MR1

Abstract: SummaryMHC class I-related gene protein (MR1) is a non-polymorphic MHC class IB antigen-presenting molecule that is the restricting molecule for mucosal-associated invariant T (MAIT) cells, a prominent population of innate-like antibacterial T cells. The MAIT cell-MR1 axis represents a new paradigm in antigen presentation, with the MR1 ligand derived from vitamin B compounds or their metabolic precursors. Many bacteria and some fungi produce the activating ligand for MR1. In evolution, MR1 is highly conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 67 publications
(197 reference statements)
2
42
0
Order By: Relevance
“…In this study, pre-incubation of a bronchial epithelial cell line with 6-FP overnight enhanced the presentation of exogenous ligand but did not affect MR1T activation in response to Mycobacterium tuberculosis ( Mtb) infection. This supports a model in which pre-incubation with MR1-stabilizing ligand brings MR1 to the cell surface and from there into an exchange compartment where it can be re-loaded with exogenous antigen [( 20 , 22 ); Figure 1 , “exchange pathway”]. This model is consistent with work from McWilliam et al, who showed that re-loading of 6-FP-bound molecules was possible at 37°C but not on ice, indicating a requirement for internalization and recycling for ligand exchange to occur ( 41 ).…”
Section: Distinct and Complementary Mr1 Antigen Presentation Pathwayssupporting
confidence: 76%
See 2 more Smart Citations
“…In this study, pre-incubation of a bronchial epithelial cell line with 6-FP overnight enhanced the presentation of exogenous ligand but did not affect MR1T activation in response to Mycobacterium tuberculosis ( Mtb) infection. This supports a model in which pre-incubation with MR1-stabilizing ligand brings MR1 to the cell surface and from there into an exchange compartment where it can be re-loaded with exogenous antigen [( 20 , 22 ); Figure 1 , “exchange pathway”]. This model is consistent with work from McWilliam et al, who showed that re-loading of 6-FP-bound molecules was possible at 37°C but not on ice, indicating a requirement for internalization and recycling for ligand exchange to occur ( 41 ).…”
Section: Distinct and Complementary Mr1 Antigen Presentation Pathwayssupporting
confidence: 76%
“…Only when exogenous ligand neutralizes the positive charge on the K43 residue in the MR1 binding groove can the protein associate with β 2 m and acquire the ability to leave the ER and translocate to the cell surface ( 38 , 41 ) ( Figure 1 , “ER pathway”). MR1 loading in this model is thought to take place in the ER, although the mechanism by which the MR1 ligand reaches this compartment is still unclear ( 22 , 38 ). This pathway has been the subject of excellent previous reviews to which we refer the reader [Example: ( 43 )].…”
Section: Distinct and Complementary Mr1 Antigen Presentation Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We further identified that MR1 mainly expressed in CD68 + Kupffer cells by immunofluorescence (Figure 3D ). It has been reported that when APCs are stimulated, MR1 molecule traffics to the cell surface from the endoplasmic reticulum to present antigen to MAIT cells ( 22 ). To study if FFA can induce MR1 expression on the surface of Kupffer cells, we stimulated CD14 + monocytes-derived macrophages with long chain fatty acids in vitro ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…This TCR structure restricts them to the nonpolymorphic, major histocompatibility complex class I-related protein, MR1, which presents bacterial-derived ligands and is expressed by a broad range of both hematopoietic and nonhematopoietic cell types. [18][19][20][21][22][23] During a UTI, murine MAIT cells have been shown to migrate to the bladder to decrease the bacterial load. In the same study, MR1 −/− mice suffered from more severe UTIs than mice in which MAIT cells were present in higher numbers.…”
Section: Introductionmentioning
confidence: 99%